Appendix 4.9: Marcos Diary Entry, 24 September 1972 - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies, 2017)
Ferdinand Marcos here claims that he was ready to disregard constitutionality—i.e., establishing a revolutionary government—if the Supreme Court justices opposed his recent martial law declaration, but the justices “insisted that we retain the color of constitutionality for everything that we do.” He decries the justices’ adherence to “technical legalism.” It nevertheless seems unlikely that he would have abandoned legality, given his previous actuations; Marcos may have been bluffing. The entry also shows the extent of Marcos’s use of the armed forces in the early days of the dictatorship—even the Reserve Officers’ Training Corps were deployed for graffiti clearing.